2017
DOI: 10.3390/rs9070661
|View full text |Cite
|
Sign up to set email alerts
|

Developing the Remote Sensing-Gash Analytical Model for Estimating Vegetation Rainfall Interception at Very High Resolution: A Case Study in the Heihe River Basin

Abstract: Accurately quantifying the vegetation rainfall interception at a high resolution is critical for rainfall-runoff modeling and flood forecasting, and is also essential for understanding its further impact on local, regional, and even global water cycle dynamics. In this study, the Remote Sensing-based Gash model (RS-Gash model) is developed based on a modified Gash model for interception loss estimation using remote sensing observations at the regional scale, and has been applied and validated in the upper reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…As reviewed by Kool et al (), despite measurement variability of ∼30%, the past studies showed over 90% agreement for ET = E + T without considering other possible sources (e.g., interception). Previous investigations indicated that forest ecosystems have larger interception ratio, but for grassland ecosystems the contribution of interception loss to total ET is much smaller (Cui et al, ). In arid areas, where precipitation is rare, canopy‐intercepted precipitation contribution to total ET is small and can be negligible (Wang et al, ).…”
Section: Introductionmentioning
confidence: 98%
“…As reviewed by Kool et al (), despite measurement variability of ∼30%, the past studies showed over 90% agreement for ET = E + T without considering other possible sources (e.g., interception). Previous investigations indicated that forest ecosystems have larger interception ratio, but for grassland ecosystems the contribution of interception loss to total ET is much smaller (Cui et al, ). In arid areas, where precipitation is rare, canopy‐intercepted precipitation contribution to total ET is small and can be negligible (Wang et al, ).…”
Section: Introductionmentioning
confidence: 98%
“…RI was estimated using the RS-Gash model (see supplementary methods), which has been proven its usability at the watershed and global scale [17][18][19][20][21].…”
Section: Ri and Water Supplymentioning
confidence: 99%
“…With the development of remote-sensing technology, experts and institutions have recently performed studies on the estimation of RI at a regional scale. The technique of RI estimation at the regional scale based on multisource remotesensing data, represented by the RS-Gash model, has been well-established, widely validated, and used in the watershed or global scale [17][18][19][20][21]. However, the investigation of the spatial heterogeneity of the factors driving RI changes based on high-resolution RI data needs to be strengthened.…”
Section: Introductionmentioning
confidence: 99%
“…Many scientists have attempted to find a cost-effective approach in documenting changes over large geographic regions in both time and space [2,[12][13][14]. Modeling has become an effective tool in understanding the spatial distribution of canopy interception at a larger scale [6,15,16]. Many models of the rainfall interception process have been developed [17][18][19].…”
Section: Introductionmentioning
confidence: 99%